Triticum aestivum L. subsp. aestivum CWI 42879 ... - GLIS Of The ITPGRFA (Centro Internacional de Mejoramiento de Maíz y Trigo, 2017)
Plant Genetic Resource. Taxonomy: Triticum aestivum L. subsp. aestivum Common name(s): Wheat Other names: STORMSVALE Conserved by: Centro Internacional de Mejoramiento de Maíz y Trigo (CIMMYT), Mexico Local sample unique identifier: CWI 42879 Method of creation: Acquisition Date: 1991 Other identifiers: n/a,CWI42879, n/a,SVALE, n/a,GID 133891, n/a,CID 124041 SID 0, n/a,CD81047 Historical: No Biological status: Advanced or improved cultivar MLS status: Included ...